Analisis Tata Kelola Perusahaan Terhadap Kebangkrutan Perusahaan yang Terdaftar di Bursa Efek Indonesia - Robby Krisyadi; Selin Selin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine whether corporate governance has an effect on the risk of corporate bankruptcy. The variables of corporate governance assessment include audit committee attendance, audit committee size, audit committee independence, audit committee expertise, audit committee meetings, board independence, and board size. The variable of corporate bankruptcy is measured based on the issuance of the financial statements for two consecutive years between experiencing profit or loss, so this study uses the logistic regression method. The population used comes from non-financial data of companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The results show that audit committee size, audit committee independence, frequency of board meeting have a significant negative effect on corporate insolvency.